Outcomes of astigmatic correction with and without two different cyclotorsion compensation methods in small incision lenticule extraction surgery - Jiping Xu; Manli Liu; Quan Liu (Photodiagnosis and Photodynamic Therapy)
Purpose: To compare the astigmatic correction outcomes of small incision lenticule extraction (SMILE) surgery with or without two different cyclotorsion compensation methods. Methods: This is a prospective randomized clinical trial. Patients with myopic astigmatism that underwent SMILE surgery were randomly divided into static cyclotorsion compensated group (SCC group), slit-lamp group and control group. In the SCC and slit-lamp groups, the intraoperative cyclotorsion was manually compensated with different limbal marking methods. In the control group, the cyclotorsion was not compensated. Visual acuity and manifest refraction were measured preoperatively and postoperatively. Astigmatic outcomes were estimated with vector analysis. Results: A total of 94 eyes from 94 patients were analyzed postoperatively at the 3-month follow-up. Their mean preoperative cylinder was -1.56±0.86 D (range: -4.25 to -0.25 D). The mean preoperative spherical equivalent was -5.95±1.72 D (range: -10.50 to -2.75 D). All groups showed favorable results in the correction of myopic astigmatism. No statistically differences were found among three groups in postoperative visual acuity, refractive outcomes or vector parameters. Conclusion: Cyclotorsion compensation with two different manual limbal marking methods was helpful in aligning the surgical position in SMILE, but it was not as effective as expected for the correction of myopic astigmatism under well controlled surgical positioning.